(untitled) (Health Renaissance, 2015)
Background: Estimation of age has been a major factor in identification of an individual, either living or after death. Objective: To estimate and assess the dental age of children by measuring the open apices of the teeth using panoramic radiograph applying linear regression equation. Methods: This was a retrospective cross-sectional study conducted on 50 children (25 boys and 25 girls) aged between 5-15 years. The seven left permanent mandibular teeth were assessed using panoramic radiographs which were collected from Medical Record Department, Manipal University, taken during the course of diagnosis and treatment. The number of teeth with closed apical and with open apical end of roots were examined and measured. The values were tabulated and placed on the linear regression equation proposed by Cameriere et al for the estimation of dental age. Result: The result showed no significant difference between the dental age (10.13±1.69 years) and the chronological age (10.31±1.75 years) (p=0.26). The method underestimated the mean age by 0.11 years and 0.23 years for the boys and girls, respectively. The paired sample t- test showed no significant difference between dental age and chronological age for boys (p=0.546) as well as for girls (p=0.351) Conclusion: The estimated age of children by measuring the open apices of the teeth using panoramic radiograph linear regression equation used in the European subjects closely matches with the chronological age in Asian subjects also. Keeping in context to validate more accurately the significance of linear regression equation, there is a need of larger sample size belonging to variety of ethnic and socioeconomic background. DOI: http://dx.doi.org/10.3126/hren.v12i1.11983 Health Renaissance 2014;12(1):33-37